Penerapan Nilai-nilai Akhlak dalam Surah Al-Ahqaf Ayat 15 untuk Membangun Karakter Mulia Anak - Dina Qomariyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The decline in morality within families due to technological advancements that reduce interaction among family members demands a character education-based approach. This study aims to analyze the application of moral values in Surah Al-Ahqaf verse 15, such as filial piety, patience, gratitude, and wisdom, in shaping the noble character of children. This research employs a qualitative method with a thematic approach based on library research, involving the analysis of Qur’anic verses and related literature. The findings show that the moral values in Surah Al-Ahqaf verse 15 can be applied through strengthening family relationships, training emotional control in children, fostering gratitude, and guiding decision-making. These values provide a solid moral foundation for educating children to become individuals of noble character. This study concludes that the application of Qur’anic values contributes to the formation of children’s noble character while also serving as an effective solution to address the moral crisis in families.